Pauline Cook Hall, A bibliography of Spanish linguistics: Articles in serial publications. Linguistic Society of America, Baltimore, 1956; 162 pp. (Supplement to Language, Vol. 32, No. 4; Language Dissertation No. 54). - Lope Blanch, Juan M. (El Colegio de México, 1957)
Se reseñó el libro: A bibliography of Spanish linguistics: Articles in serial publications.